New Advances of CRISPR/Cas9 Technique and its Application in Disease Treatment and Medicinal Plants Research - Wan, He-Fang; Han, Wen-Jing; Zhou, Lei; Wang, Shuo; Sui, Chun (Current Pharmaceutical Biotechnology, 2022)
Background: Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/Cas9 technology is widely used in disease treatment and medicinal plant improvements due to its advantages, such as easy operation, low time consumption, and high efficiency. However, potential off-target risks still exist in practical applications and need to be solved urgently. Objectives: This study aimed to review the application progress of CRISPR/Cas9 technology in the field of disease treatment and medicinal agriculture in recent years. Furthermore, the study discusses the ways to reduce the off-target effect of CRISPR/Cas9 technology, providing a reference for the further application of this technology. Methods: CiteSpace software was used to analyze relevant literature data from 2013 to August 2021, and search results were retrieved from Web of Science, PubMed, and CNKI databases. Results: In the field of disease treatment, CRISPR/Cas9 technology has great potential to cure challenging human diseases and has been widely used in drug target development, drug design, and screening. In crop breeding, CRISPR/Cas9 accelerates the improvement of crop varieties and shortens the number of years of crop breeding. By adjusting the length and GC content of sgRNA and changing the concentration of Cas9/sgRNA complex to reduce the off-target effect of CRISPR/Cas9 technology, the target genes can be manipulated more accurately. Conclusion: CRISPR/Cas9 technology is an indispensable and key technology in the field of disease treatment and medicinal plants. With the in-depth study of the off-target effect, CRISPR/Cas9 technology can have broader application prospects in the fields of medicine and medicinal agriculture.
Keywords: sgRNA